Konsep Islam Rahmatān Lil ‘Alamīn Dalam Al-Qur’an (Perspektif Tafsir Kontekstual Abdullah Saeed) - Nahwa Faadlil Basya; Muhammad Irfan Riyadi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research is motivated by the rise of violence committed in the name of religion, both in the real world and online. Such violence is driven by a misinterpretation of Qur'anic texts and certain ideologies that reject diversity. The main focus of this study is to explore the meaning and contextualization of the values of Islam rahmataān lil ‘alamīn as found in the Qur’an, using Abdullah Saeed’s contextual interpretation approach. This research employs a qualitative library-based method with descriptive and deductive analysis. The findings reveal that Islam rahmataān lil ‘alamīn encompasses values of compassion, justice, brotherhood, and noble character. The contextualization of these values in the modern era includes: (1) the social aspect, which serves to counter radicalism and promote tolerance; (2) the educational aspect, by integrating these values into Islamic curricula; (3) the economic aspect, through community empowerment; and (4) the aspect of religious moderation, by introducing moderate values early in Islamic education